Faktor-faktor yang Menyumbang kepada Bencana Banjir di Kawasan Taman Nira, Batu Pahat, Johor. - Mohd Fuad, Siti Nurhaliza; Shafii, Haryati; Ta Wee, Seow; Mohamed, Sulzakimin; Sarpin, Norliana; Kai Chen, Goh (Research in Management of Technology and Business, 2023)
A disaster is an event that occurs suddenly and causes many lives to be lost as well as loss of property and the daily activities of the people involved will be affected. The problem for this study is issue of "Flooding" that often occurs in Taman Nira, Batu Pahat, Johor due to various factors and causes various effects on the physical and human environment. The objective of this study is to identify the factors that contribute to the flood disaster in Taman Nira, Batu Pahat, Johor, to study the effects of the flood disaster in the area on the physical and human environment  and to examine the effectiveness of the management of DPS and PBT to overcome the flood disaster in Taman Nira, Batu Pahat, Johor. Quantitative methods that are the distribution of questionnaires and qualitative methods by holding interview sessions have been done for this study to obtain the necessary information. The results of the study show that there are various factors that contribute to the flood disaster that occurred in Taman Nira, Batu Pahat Johor, it is physical factors and human factors. The physical factors are the rapid and uncontrolled development, high tides that occur when it rains, the small size of the drainage basin, and the low and easily flooded areas of the houses. While the human factors are the rapid and uncontrolled development which is a factor in the occurrence of floods, lack of drainage infrastructure, unorganized garbage disposal and unscheduled maintenance of the drainage system. In conclusion, there are several recommendations that can be made by the authorities and the local population, among them is that the authorities regularly monitor periodically and make preliminary preparations such as dredging rivers or ditches before the occurrence of high tides and heavy rains while the community needs to maintain cleanliness in the drainage area with how not to throw garbage into drains and rivers to avoid clogging drainage areas.